2005
DOI: 10.1177/104063870501700315
|View full text |Cite
|
Sign up to set email alerts
|

Acute Depigmentation of Fertile Brown Eggs in a Commercial Layer Operation

Abstract: Abstract. Rapid depigmentation of brown eggs is an infrequent but startling event in the commercial egg industry that can result in significant economic losses. Loss of shell pigment in brown-shelled eggs is caused by various factors. In many cases, the exact cause of flock-wide pigment loss remains undetermined. A rapid decline in shell pigmentation was observed in 2 flocks of Hyline brown layers. The lack of evidence of an infectious disease process suggested a feed or management problem. On the basis of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Avian diseases such as infectious bronchitis and Newcastle disease may cause eggshell thinning, which may subsequently affect eggshell color (Charlton et al, 2005). Medications, such as nicarbazin, may inhibit or discolor brown eggshells (Charlton et al, 2005). While the actual color of the eggshell is a genetic factor, it is suggested that eggshell discoloration is also genetically linked.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Avian diseases such as infectious bronchitis and Newcastle disease may cause eggshell thinning, which may subsequently affect eggshell color (Charlton et al, 2005). Medications, such as nicarbazin, may inhibit or discolor brown eggshells (Charlton et al, 2005). While the actual color of the eggshell is a genetic factor, it is suggested that eggshell discoloration is also genetically linked.…”
Section: Introductionmentioning
confidence: 98%
“…The effect of eggshell color has also been extensively evaluated as a means of determining egg quality in broiler breeders (Joseph et al, 1999), which are also predominately brown egg layers. In addition, eggshell color may also be an indicator in the health and stress status of layers (Charlton et al, 2005;Mertens et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation